53.2k views
3 votes
Solve the system using elimination.

3x – 4y = 9
–3x + 2y = 9

(–3, –6)

(–9, –9)

(–27, –9)

(3, 9)

User OlliM
by
4.4k points

1 Answer

4 votes

Answer:

(- 9, - 9)

Explanation:

Given the 2 equations

3x - 4y = 9 → (1)

- 3x + 2y = 9 → (2)

Adding (1) and (2) will eliminate the term in x

(1) + (2) term by term

(3x - 3x) + (- 4y + 2y) = (9 + 9)

0 - 2y = 18

- 2y = 18 ( divide both sides by - 2 )

y = - 9

Substitute y = - 9 into (1) or (2) and evaluate for x

(1) → 3x + 36 = 9 ( subtract 36 from both sides )

3x = - 27 ( divide both sides by 3 )

x = - 9

Solution is (- 9, - 9)

User Jonathan Beebe
by
4.0k points